2010
DOI: 10.1093/rheumatology/keq194
|View full text |Cite
|
Sign up to set email alerts
|

Benefits 8 years after a remission induction regime with an infliximab and methotrexate combination in early rheumatoid arthritis

Abstract: A remission induction regime with an INF-MTX combination for 1 year in early RA can improve long-term clinical outcomes. Larger studies will be required to confirm the implications of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 11 publications
2
33
0
2
Order By: Relevance
“…Patients treated with MTX alone, even when achieving remission, will demonstrate progression of damage predicted by subclinical synovitis (103). Long-term data of early remission induction are now available showing long-term benefits (104). For patients with RA, clinical features are insufficient to give an accurate picture of the disease state (105), and joint damage has been shown to progress despite a sustained clinical remission in early rheumatoid arthritis patients after etanercept interruption (106).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Patients treated with MTX alone, even when achieving remission, will demonstrate progression of damage predicted by subclinical synovitis (103). Long-term data of early remission induction are now available showing long-term benefits (104). For patients with RA, clinical features are insufficient to give an accurate picture of the disease state (105), and joint damage has been shown to progress despite a sustained clinical remission in early rheumatoid arthritis patients after etanercept interruption (106).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…A number of reports have described the long-time effectiveness of biologic treatment from two to as long as eight years. Although treatment regimens vary, it has been shown that early and maintained targeted treatment using biologic agents has functional and radiological benefits (68)(69)(70).…”
Section: Biological Agents Targeting Cytokinesmentioning
confidence: 99%
“…Higher rates of remission have been achieved [48], and sustained remission despite withdrawal of TNFi therapy is more readily achievable [49,50]. Evidence supporting the early use of TNFi, before the failure of conventional DMARDs, is increasing such that recent recommendations by the European League Against Rheumatism (EULAR) suggest the use of TNFi therapy in combination with MTX as first-line therapy in patients with poor prognostic signs for rapidly progressive disease, such as early radiographic damage or very high disease activity [51].…”
Section: Future Perspectivementioning
confidence: 99%